A Contemporary Archaeology of London's Mega Events From the Great Exhibition to London 2012 - Gardner, Jonathan (UCL Press, 2022)
A Contemporary Archaeology of London's Mega Events explores the traces of London's most significant modern 'mega events'. Though only open for a few weeks or months, mega events permanently and disruptively reshape their host cities and societies: they demolish and rebuild whole districts, they draw in materials and participants from around the globe and their organisers self-consciously seek to leave a 'legacy' that will endure for decades or more. With London as his case study, Jonathan Gardner argues that these spectacles must be seen as long-lived and persistent, rather than simply a transient or short-term phenomena. Using a novel methodology drawn from the subfield of contemporary archaeology - the archaeology of the recent past and present-day - a broad range of comparative studies are used to explore the long-term history of each event. These include the contents and building materials of the Great Exhibition's Crystal Palace and their extraordinary 'afterlife' at Sydenham, South London; how the Festival of Britain's South Bank Exhibition employed displays of ancient history to construct a new post-war British identity; and how London 2012, as the latest of London's mega events, dealt with competing visions of the past as archaeology, waste and 'heritage' in creating a vision of the future. This book offers significant new directions for the study of mega events in its comparison of how three mega events changed London over three centuries. Drawing on a broad range of theoretical and methodological frameworks and a rich array of sources, it demonstrates the great potential of contemporary archaeology for understanding contemporary urban phenomena.